A gene signature distinguishing CD133hi from CD133- colorectal cancer cells: essential role for EGR1 and downstream factors - Ernst, Aurélie; Aigner, Maximilian; Nakata, Susumu; Engel, Felix; Schlotter, Magdalena; Kloor, Matthias; Brand, Karsten; Schmitt, Steffen; Steinert, Gunnar; Rahbari, Nuh Nabi; Koch, Moritz; Radlwimmer, Bernhard; et al. (Pathology, 2011)
Aims - In colorectal cancer (CRC), CD133 expression is an independent prognostic marker associated with adverse clinical outcome. The CD133 epitope AC133 allowed isolating stem cells from normal and cancerous tissues, although its use in colon was questioned. We aimed to identify differences between AC133hi and AC133- cells. - Methods - We analysed the gene expression profiles of EpCAM+/CEA+/AC133hi and EpCAM+/CEA+/AC133- cells from primary CRC and liver metastasis tissues (n=5). Immunohistochemistry confirmed these results in a validation set. - Results - We identified 68 genes differentially expressed between both populations, including genes of notorious importance in CRC pathogenesis, and several candidates not previously shown to play a major role in CRC. Notably, EGR1 belonged to the most highly expressed genes in AC133hi cells. In the validation set, the presence of EGR1 and CD133 correlated (r=0.625). Since EGR1 regulates Wnt through up-regulation of TCF4, which induces stem cell marker LGR5, the potential association between LGR5, EGR1 and CD133 was investigated. The presence of LGR5 correlated with the presence of EGR1 and CD133. Strong signals for LGR5 were detected throughout tumour invasion fronts. - Conclusions - The study suggests a connection between CD133 and EGR1 and emphasises the importance of the EGR1/TCF4/CD133/LGR5 network in CRC.